2014
DOI: 10.1186/1472-6939-15-3
|View full text |Cite
|
Sign up to set email alerts
|

Information disclosure in clinical informed consent: “reasonable” patient’s perception of norm in high-context communication culture

Abstract: BackgroundThe current doctrine of informed consent for clinical care has been developed in cultures characterized by low-context communication and monitoring-style coping. There are scarce empirical data on patients’ norm perception of information disclosure in other cultures.MethodsWe surveyed 470 adults who were planning to undergo or had recently undergone a written informed consent-requiring procedure in a tertiary healthcare hospital in Saudi Arabia. Perceptions of norm and current practice were explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
1
23
1
Order By: Relevance
“…Arab countries, including Saudi Arabia have been characterized by high-context communication culture [ 44 ] and blunting coping style, [ 45 ] and it was hypothesized that in such cultures using “Western” reasonable patient standard of information disclosure may not be appropriate [ 46 ]. The results of this study and our previous study on desired information disclosure in clinical informed consent [ 47 ] are not consistent with such hypothesis. Interestingly, governing codes on disclosure of terminal illness to patients and families in Islamic countries vary considerably [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Arab countries, including Saudi Arabia have been characterized by high-context communication culture [ 44 ] and blunting coping style, [ 45 ] and it was hypothesized that in such cultures using “Western” reasonable patient standard of information disclosure may not be appropriate [ 46 ]. The results of this study and our previous study on desired information disclosure in clinical informed consent [ 47 ] are not consistent with such hypothesis. Interestingly, governing codes on disclosure of terminal illness to patients and families in Islamic countries vary considerably [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“… 22 Deferred consent seemed to initially perturb some parents, who spoke of their momentary shock or anger when they first found out that their child had been entered into research without their prior knowledge and consent. 42 Many parents were surprised that the normal process of research information disclosure as part of an informed consent process could be changed and postponed in this way, 40 43 while a few suggested that their right as a parent to make an autonomous decision about research had or could have been taken away. 5 44 45 Practitioners did not describe these initial negative reactions from parents, suggesting that parents did not voice these concerns during recruitment discussions.…”
Section: Discussionmentioning
confidence: 99%
“…More elder educated males are particularly sensitive regarding the disclosure of their confidential information [22]. Aesthetic-seeking patients trust their medical aesthetician.…”
Section: Principle Of Respect and Confidentialitymentioning
confidence: 99%